A polifonia do cordel de simbólica católica: contrapondo reducionismos interpretativos - Santos, José Carlos Cariacás Romão dos (2010)
The aim of this thesis is to analyse the reductionist presuppositions about cordel (pamphlet) literature in its religious dynamic. We examine the hypothesis that the cordel is a polyphonic product and that therefore it must be analysed in such a way as to avoid simple general statements in respect of its production. 　 We begin our research with a deep examination of the world of the cordel and the problems inherent in its interpretation, targeting, to begin with, the poor usage of the terms people/popular in the understanding of the cordel, which in its turn cancels out the complexity of perception of the listeners for whom the poems were written. Next we look at the precariousness of the classification of the religious cordel which only deals with elements outside of the context without getting caught up in the internal dynamic of its production. In three chapters we discuss the fallacy that asserts the production of the cordel to be coloured by catholic orthodoxy, thus analysing human images as if they are thoughts in the same production (with a view to counterpoint the reductionist interpretation). In the last chapter we analyse and refute the exaggerated suggestion that the cordel is conservative and traditionalist. 　 The research uncovers the following results: the cordel is a polyphonic product with its own internal logic and which does not offer any margin for reductionist interpretation. Any reductionism is due to the intellectual short-sightedness of researchers-once they are shown to be ignorant of religious phenomena and theoretical articulations concerning the culture of popular religion. The work in question offers information for the process of interpretation of catholic symbolism in the cordel